Should Non-EU Countries Be Able to Join the EU Emissions Trading System? - Jochen Andritzky; Nils Hesse (Intereconomics, 2025)
Climate mitigation requires global action: it does not matter where on earth a tonne of carbon emissions is being saved. Reducing carbon emissions is often cheaper in less developed countries than in EU member states. Therefore, integrating them into the EU Emissions Trading System generates efficiency gains that present a triple win for both regions and the global climate while also addressing the development dilemma of climate mitigation.
Keywords: F18; Q58; 330